Image encryption under spatial domain based on modify 2D LSCM chaotic map via dynamic substitution-permutation network - Mohammed, Rana Saad; Jabbar, Khalid Kadhim; Hilal, Hussien Abid (Institute of Advanced Engineering and Science, 2021)
Image encryption has become an important application aspect of information security. Most attempts are focused on increasing the security aspect, the quality of the resulting image, and the time consumed. On the other hand, dealing with the color image under the spatial domain in this filed is considered as another challenge added to the proposed method that make it sensitivity and difficulty. The proposed method aims to encode a color image by dealing with the main color components of the red (R), green (G), and blue (B) components of a color image to strengthen the dependence of each component by modifying a two dimensional logistic- sine coupling map (2D- LSCM). This is to satisfy the statistical features and reduce time-consumption, and benefit from a mixing step of the second of advanced encryption standard (AES) candidates (serpent block cipher) and modified it to achieve in addition of confusion and diffusion processes. The experimental results showed that our proposed method had the ability to resist against statistical attacks and differential attacks. It also had a uniform histogram, a large key space, complex and faster, closer Shannon entropy to 8, and low correlation values between two adjacent pixels compared with other methods.